Pulsed current-mode signaling for nearly speed-of-light intrachip communication. - Jose, A.P.
In this paper, we describe the design of on-chip repeater-less interconnects with nearly speed-of-light latency. Sharp current-pulse data transmission is used to modulate transmitter energy to higher frequencies, where the effect of wire inductance is maximized, allowing the on-chip wires to function as transmission lines with considerably reduced dispersion. A prototype 8-Gb/s serial link employing this pulsed current-mode signaling in a 0.18-μm CMOS process is described and measured.
Keywords: 0.18 micron; 8 Gbit/s.; CMOS process; Current-pulse data transmission; High-speed integrated circuits; Intrachip communication; On-chip repeater-less interconnects; On-chip wires; Pulsed current-mode signaling; Speed-of-light latency; Transmission lines; Transmitter energy; Wire inductance